Available Water Supplies in Beijing, China, Under Single‐ and Multi‐Year Drought. (25th March 2020) - Chang, Huanyu; Zhao, Yong; Wang, Qingming; Wang, Jianhua; Li, Haihong; Zhai, Jiaqi; Han, Jingyan; Jiang, Shan
Abstract: Since its implementation in 2015, the Middle Route of the South‐to‐North Water Diversion Project (MR‐SNWDP) has transferred an average of 45 billion cubic meters of surface water per year from the Yangtze River in southern China to the Yellow River and Hai River Basin in northern China, but how that supply is able to cope with droughts under different scenarios has not been explored. In this study, using the water demand for 2020 as the guaranteed water target, a Water Evaluation and Planning system was used to simulate available water supplies in Beijing under different drought scenarios. In the case of a single‐year drought, without the MR‐SNWDP, Beijing's water shortage ratio was 16.7%; with the MR‐SNWDP, this ratio reduced to 7.3%. In the case of a multi‐year drought, without the MR‐SNWDP, Beijing's water shortage ratio was 25.3%; with the MR‐SNWDP, this ratio reduced to 7.4% and domestic water supply was improved. Our research suggests that to prepare for multi‐year drought in the Beijing area, the SNWDP supports increased supplies to the region that would mitigate drought effects. This study is, however, mostly focused on water supply provision to Beijing and does not comprehensively evaluate other potential impacts. Multiple additional avenues could be pursued that include replenishing groundwater, increasing reservoir storage, and water conservation methods. Further research is needed to explore the relative costs and benefits of these approaches. Abstract : Research Impact Statement : Importance of the MR‐SNWDP (middle route of the South‐to‐North Water Diversion Project) for ensuring available water supplies in Beijing.